Genomic footprints of adaptation in a cooperatively breeding tropical bird across a vegetation gradient. Issue 17 (29th July 2017) - Termignoni‐García, Flavia; Jaramillo‐Correa, Juan P.; Chablé‐Santos, Juan; Liu, Mark; Shultz, Allison J.; Edwards, Scott V.; Escalante‐Pliego, Patricia
Abstract: Identifying the genetic basis of phenotypic variation and its relationship with the environment is key to understanding how local adaptations evolve. Such patterns are especially interesting among populations distributed across habitat gradients, where genetic structure can be driven by isolation by distance (IBD) and/or isolation by environment (IBE). Here, we used variation in ~1, 600 high‐quality SNPs derived from paired‐end sequencing of double‐digest restriction site‐associated DNA (ddRAD‐Seq) to test hypotheses related to IBD and IBE in the Yucatan jay ( Cyanocorax yucatanicus), a tropical bird endemic to the Yucatán Peninsula. This peninsula is characterized by a precipitation and vegetation gradient—from dry to evergreen tropical forests—that is associated with morphological variation in this species. We found a moderate level of nucleotide diversity (π = .008) and little evidence for genetic differentiation among vegetation types. Analyses of neutral and putatively adaptive SNPs (identified by complementary genome‐scan approaches) indicate that IBD is the most reliable explanation to account for frequency distribution of the former, while IBE has to be invoked to explain those of the later. These results suggest that selective factors acting along a vegetation gradient can promote local adaptation in the presence of gene flow in a vagile, nonmigratory and geographically restricted species. The putative candidate SNPs identified here are located within or linked to a variety of genes that represent ideal targets for future genomic surveys.